Low-temperature sequential deposition for efficient inverted perovskite solar cells - Mengjiong Chen; Zhenzhen Qin; Ziyang Zhang; Wenxiang Xiang; Yingming Liu; Chuang Tian; Siyuan Chen; Yanbo Wang; Liyuan Han (Nature Communications)
Abstract Inverted perovskite solar cell has made significant progress in recent years. Although two-step sequential deposition shows the benefits to obtain higher quality large-size perovskite crystals, the high annealing temperature, which is required to achieve phase transition, leads to the desorption of self-assembled molecules at the buried interface and induces redundant lead iodide at the top interface. Here, we propose a low temperature sequential deposition method by introduce a tailor-made 3-ethyl-1-methyl-1H-imidazol-3-ium dimethyl phosphate into lead iodide precursor solution to facilitate the sufficient reaction between lead iodide and organic salts, and lower the energy barrier from delta- to alpha-perovskite. As a result, highly crystallized and pure alpha-phase perovskite films with large grain size are fabricated, preventing the damage to buried self-assembled molecules and the formation of redundant lead iodide, which contributes to a high open circuit voltage of 1.21 V and a certified efficiency of 26.0%. The encapsulated devices show improved stability following ISOS-D-3 and ISOS-L-2 protocols.